Theoretical and experimental characterizations of gigahertz acoustic streaming in microscale fluids - Weiwei Cui; Wei Pang; Yang Yang; Tiechuan Li; Xuexin Duan (Nanotechnology and Precision Engineering, 2019)
Even as gigahertz (GHz) acoustic streaming has developed into a multi-functional platform technology for biochemical applications, including ultrafast microfluidic mixing, microparticle operations, and cellar or vesicle surgery, its theoretical principles have yet to be established. This is because few studies have been conducted on the use of such high frequency acoustics in microscale fluids. Another difficulty is the lack of velocimetry methods for microscale and nanoscale fluidic streaming. In this work, we focus on the basic aspects of GHz acoustic streaming, including its micro-vortex generation principles, theoretical model, and experimental characterization technologies. We present details of a weak-coupled finite simulation that represents our current understanding of the GHz-acoustic-streaming phenomenon. Both our simulation and experimental results show that the GHz-acoustic-induced interfacial body force plays a determinative role in vortex generation. We carefully studied changes in the formation of GHz acoustic streaming at different acoustic powers and flow rates. In particular, we developed a microfluidic-particle-image velocimetry method that enables the quantification of streaming at the microscale and even nanoscale. This work provides a full map of GHz acoustofluidics and highlights the way to further theoretical study of this topic. Keywords: Acoustic streaming, Gigahertz, Body force, Microfluidic PIV